Epidemiological study of gastro-esophageal reflux disease in rural population - Rokonuzzaman, SM; Bhuiyan, MR; Ali, MH; Paul, GK; Khan, MR; Mamun, AA (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jul;20(3):463-471 The abstract of this article is available on the PubMed website